Organic Waste Chopper Tool Design Using Autodesk Inventor 2015 Software - Nengah Ludra Antara (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
In the program of mechanical engineering, the software used to draw is Autodesk Inventor. Autodesk inventor is a CAD program in the program of engineering that is applied to the design of mechanics in 3D. In designing a tool, of course, it is preceded by a planned design concept. In making a design a tool requires a process or steps for making the design. These steps include the size, dimensions, and materials used in making organic waste chopper tool. The drawing process uses the 2015 Autodesk Inventor program, the first is the making of sketches, components on the machine, followed by assembly of each component, then rendering images, animation as the final stages of drawing design input into "IDW" complete with size, scale, material. Image projection to make it easier for designers to make tools. Drawings of plan and complete details covering the scale dimensions will be able to simplify the manufacturing process (production) of the components of the tool and can reduce the risk of errors in the process of making tools.